Quantifying the onset of the concentric phase of the force-time record during jumping - Jensen, R.; Leissring, S.; Garceau, L.; Petushek, E.; Ebben, W. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Knowledge of the onset of concentric movement is needed to determine many variables including rate of force development. This study sought to identify the onset of the concentric phase of the force-time record of a variety of jumps. Twelve subjects performed a depth jump, single leg countermovement jump, and a counter movement jump. Vertical ground reaction force (GRF) obtained via force plate and video analysis of a marker placed on the hip, was used to estimate the time of onset of the concentric phase on the force time record. Repeated Measures ANOVA indicated differences in the onset of the concentric phase for the different jumps. Results can be used to assist in the calculation of outcome variables based on the determination of the onset of the concentric phase of the force-time record, when motion analysis is unavailable.